Lecture Exchange Program di Politeknik Tuanku Syed Sirajuddin dalam Rangka iPROPEX 2024 Sebagai Wujud Pengabdian Global - Zuindra; Jamali (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
The Lecture Exchange Program held as part of iPROPEX 2024 aims to provide insights into the potential and opportunities of entrepreneurship in the coffee industry, specifically Aceh coffee. Through this lecture, students at Politeknik Tuanku Syed Sirajuddin gain in-depth knowledge about the history, production process, and challenges faced by the coffee industry in Aceh, as well as effective marketing and branding strategies for promoting Aceh coffee in international markets. The program also encourages students to actively engage in designing innovative ideas for coffee product development. The outcomes of this program are expected to inspire students to cultivate entrepreneurial spirit and create sustainable business opportunities in the coffee sector, ultimately contributing to both local and global economic growth.